Musical festival floats of Japan : Festival ensembles in the Chita Peninsula and Aichi - Lundström, Håkan (Lund University Press, 2025)
This book aims to increase the understanding of festival music in Japan. It is based on more than thirty years of fieldwork. Close study of one local festival in the town of Taketoyo is combined with a wider comparative analysis that covers most of the of the Aichi prefecture in central Japan. All these festivals are float-festivals. Charged with spiritual power, the floats serve as mobile shrines with musicians riding inside them. The music they play has important functions at different stages of the festivals. Drums and flutes form the core of all the ensembles, but they vary in their use of different kinds of drums and certain other instruments. Most of the festivals in the area, their music included, spread from the major town of Nagoya to surrounding districts from the seventeenth century onwards. Through oral transmission, many local variations have developed and over time have become treasured local traditions. The geographic distribution of ensemble types and individual tunes indicates certain historical relationships. These religious festivals have counterparts in many parts of the world. While strongly based in history, the Japanese festivals and their music have adapted to new circumstances throughout the centuries. From the mid-twentieth century onwards, modernization has increased. This study shows how Japanese festivals may be approached with methods from modern festival research, thereby opening new perspectives in this global field of scholarship.
Keywords: ethnomusicology; matsuri; dashi; hayashi